On Catholic LI Wenyu (1840-1911)’s View of Evolution during late Qing - XIAO, Qinghe; GUO, Jianbin (Journal of Research for Christianity in China (JRCC), 2025)
Yan Fu (1854-1921) was a significant modern translator. His Chinese version of Evolution and Ethics had greatly promoted the thought of "social evolution”, which not only provided theoretical basis for Chinese salvation, but also has positive impacts on the academic world at that time. Therefore scholars always paid close attentions to the positive influnences of the Chinese edition of Evolution and Ethics, but have little research on the reflection and refutation for Chinese Christians on this book and its thoughts such as evolution. In this paper, with focus on animadversion on Yan Fu’s Chinese version of Evolution and Ethics and Xu Liku written by the Catholic priest LI Wenyu (1840-1911), the author investigates LI wenyu’s notion of “Evolution and Ethics”. Firstly, this paper investigates the concept of “origin of species”. LI wenyu thought that everything in the world was created by the God, and then primitive material was just initial state of all things and a necessary condition for the composition of other substances. Primitive material was not existed inherently. Although it had raw power, it didn’t prompt the biodiversity. Because all kinds of species in the world, each with features, it could carry out their duties and orderly thrive according to law of development, only the God had the power to create everything. Secondly, the people who supported the evolution thought that creature always followed the law that everything is inanimate to animate and no spirituality to having spirituality in the course of biological evolution. That is called “Metaplasia ” and “changes in species”. Citing Louis Pasteur’s experimental results and combining with logical reasoning, LI wenyu thought that all creatures are derived from their own seeds or spawns instead of “Metaplasia”. At the same time, he thought there is strictly distinction between humans and animals. Comparing with external characteristics between humans and monkeys and combining the truth that there’s lack of fossil of “transitional species” in the strata, he manifested monkeys never evolved into humans. Meanwhile he also defined the “kind” to further refute the” changes in species”. In a word, he proved the God create all creatures through refuting “Metaplasia” and “changes in species”. At last, the study of LI wenyu’s “concept of evolution” helps to enrich the academic study on “Enlightenment Thought” as well as the history of the Catholic Church in China.